Comparative Analysis of ROA, ROE, and GDP on Stock Returns in Sharia and Non-Sharia Food & Beverage Firms - Prasetyo, Bintang Dwi; Tripuspitorini, Fifi Afiyanti; Purbayati, Radia; Kusnadi, Hani Kustyanti; Nuzul, Dinda Amanda Ainun (Journal of Applied Islamic Economics and Finance, 2025)
This study examines the comparative influence of Return on Assets (ROA), Return on Equity (ROE), and Gross Domestic Product (GDP) on stock returns in sharia-compliant and non-sharia food and beverage companies listed on the Indonesia Stock Exchange (IDX) and the Indonesia Sharia Stock Index (ISSI) from 2020 to 2023. Using a quantitative descriptive method, the research applies panel data regression analysis with EViews 12 on secondary data obtained from annual reports and the Central Statistics Agency (BPS). The study sample comprises 10 sharia and 8 non-sharia companies selected through purposive sampling. The findings show that for sharia companies, ROA significantly affects stock returns, while ROE and GDP do not. In contrast, for non-sharia companies, none of the variables significantly affect stock returns. These results indicate a divergence in stock return determinants based on the company’s sharia status. The study provides insights for investors and companies in managing financial performance and investment decisions.